Breve história da otorrinolaringologia: otologia, laringologia e rinologia - Nogueira Júnior, João Flávio (2007)
Ears, nose and throat have intrigued humanity since immemorial times. Treatments for the larynx, the nose and the ear and also surgeries were practiced by Greek, Hindu and Byzantine doctors. In the 20th century clinical and surgical innovations were incorporated, thanks to new anesthesia techniques, antibiotics, radiology and new technologies. AIM AND METHOD: show the evolution of this science throughout the times, recognizing important persons in otology, rhinology and laryngology. RESULTS AND CONCLUSION: Understanding the evolutions in clinical and surgical anatomy, physiology, treatment modalities, and the personalities that lead to these advances is of great importance for the evolution of medical science. Otorhinolaryngology has a very rich history, with important collaborators and personalities in the history of medicine. The specialty was one of the first to use local anesthesia for procedures, pioneer in treatments with devices that recouped hearing and the use of microscopes in surgeries. Few medical specialties had suffered as many changes and scientific developments in these last decades as Otorhinolaryngology had, with the advantage of incorporating technologies such as endoscopy, radiology, microsurgery and information technology.